DNA barcoding of medically-important arthropods including molecular detection of associated potential pathogens in head lice / Aida Syafinaz Mokhtar - Aida Syafinaz, Mokhtar (2017)
Ectoparasitic infestation of humans is of particular interest because some species can act as vectors of pathogens resulting in wide-ranging pathogenic effects. Identification of ectoparasites using morphological keys is not applicable in some instances, especially if the ectoparasite specimen is damaged or in an immature state of development. DNA barcoding serves as an alternative technique to identify ectoparasite specimens to species by using a fragment of cytochrome c oxidase subunit I (COI) mitochondrial gene as an identification key. Similarly, isolation of pathogens from ectoparasites is tedious and time-consuming, therefore a molecular approach is preferred as it offers rapidity, specificity and sensitivity. The main objective of this thesis is to determine the genetic diversity of medically-important ectoparasites and their associated pathogens in welfare homes from two different geographical areas of Peninsular Malaysia. People living in welfare homesare prone to ectoparasitic infestation as they live in densely packed institutions, often with unhygienic practices, therefore identification of ectoparasite species and any pathogens these ectoparasites might harbour is crucial to avoid transmission of diseases among occupants. The identification of arthropod specimens, submitted to the Department of Parasitology,in medical case reports was also attempted and discussed. A total of 900 head lice and 26 bedbugs were collected from 15 welfare homes across Greater Kuala Lumpur/Klang Valley (KL/KV) and 832 head lice were collected from 10 welfare homes across Kedah. Pediculosis infestation rates ranging from 13.0% to 100% and 34.3% to 100% in Greater KL/KV and Kedah, respectively. DNA barcoding identified the head lice, Pediculus humanus capitis collected from both areas as belonging to three clades corresponding with three Barcode Index Numbers (BINs) in the Barcode of Life Datasystems (BOLD): Clade A (41%) (=BOLD: AAA1556), Clade B (2%) (= BOLD: AAA1557) and Clade D (57%) (=BOLD:AAW5034). Nine welfare homes in Greater iv KL/KV and seven welfare homes in Kedah had head lice from multiple clades. Head lice of Clade B and Clade D were found living on the same human head at Pusat Jagaan Nuri welfare home in Kuala Lumpur. DNA fromAcinetobacter spp. wasdetected in 52 (20%) head lice belonging to clade A and D and were identified as Acinetobacter guillouiae (8.5%), Acinetobacter junii (6.2%), Acinetobacter baumannii (3.8%), and Acinetobacter nosocomialis (1.5%). In addition, DNA from Serratia marcescens was detected in five (1.9%) head lice and DNA from Staphylococcus aureus was detected in 20 (7.7%) head lice. DNA barcoding confirmed the bedbugs collected from a single welfare home in Kuala Lumpur as beingCimex hemipterus (BOLD ID:BBCH001-16). DNA barcoding identified arthropod specimens presented to the Department of Parasitology in three medical case reports as ticks of the genus Dermacentor, larvae of filter fly Clogmia albipunctatus and larvae of cigarette beetle Lasioderma serricorne. This is the first report on the genetic diversity of head lice in Malaysiathrough DNA barcoding; as well as the first to provide molecular evidence on the type of bacteria occurring in head lice, suggesting potential transmission of these pathogens to Malaysian populations. The data obtained provide fundamental data so that necessary planning, funding and control measures can be undertaken by the health authorities to prevent the occurrence of head lice infestations in welfare homes. It is anticipated that the DNA barcoding technique used in this study is able to provide rapid and accurate identification of arthropods especially of the medically-important ones.